Using motion sensor technology to manage risk of injury in a strength and conditioning program for female collegiate athletes - Garner, J. C.; Parrish, L. R.; Shaw, K. R.; Wilson, S. J.; Donahue, P. T. (International Journal of Kinesiology & Sports Science, 2020)
Background of Study: Females generally have a 6-8 times higher risk for lower extremity injury compared to male counterparts due to biomechanical differences and/or poor landing strategies. In recent years, a great deal of focus has been placed on prevention and reduction of non-contact lower extremity injuries. This has spurred the development of assessment methods to determine how athletes move and tools with which those motions are measured. Efforts have been made to measure and quantify movement strategies, which have given rise to multiple movement tests and measurement devices. One approach is the use of wearable technologies used in conjunction with a movement screening. Objective: Demonstrate a practical approach of using wearable technologies to guide training regimens in a population of female athletes that would be considered at risk for lower extremity injuries. Methods: A cohort of Division I female volleyball athletes were screened using wearable technology then assigned an intervention based on screening results. Comparisons were made between injury rates during the season when the intervention was applied compared to previous seasons. Results: All lower extremity injury rates were reduced after the intervention was applied. Conclusions: The use of wearable technology aids in quantifying movement to then assign a strategic intervention to reduce injuries in an at risk athletic population.